Natural ventilation analysis in a Social Housing Program with different wall configurations through CFD simulations - Xavier, Ana Clara de Almeida; Lukiantchuki, Marieli Azoia (Risco - Journal of Architecture and Urbanism, 2021)
Natural ventilation is an efficient strategy for passive thermal conditioning of buildings. However, this resource is often underused in social housing (HIS), characterized by standard projects without considering the region's climatic characteristics. In addition, these houses are set up in small lots with the presence of walls for the residents' security and privacy, significantly impacting on the use of external winds. The article discusses how HIS projects are very underutilized from the point of view of natural ventilation, since the use of simple and low-cost strategies helps with thermal comfort in addition to maintaining the safety and privacy of residents, such as the use of permeable walls.